Identifying consumer openness to new ingredients: A conjoint study on consumer segments in the UK - Altintzoglou, Themistoklis; Heide, Morten (Frontiers in Aquaculture, 2023)
The aim of this study was to explore consumer acceptance of food products that make use of ingredients from underutilized marine species. As these species are not commonly used as ingredients in food products, a goal of this study was to explore how relevant personality factors influenced the acceptance of such products. This would be achieved by (a) identification of consumer segments based on the personality factors–domain specific innovativeness, food technology neophobia, health involvement, and disgust, (b) description of the main characteristics of these consumer segments, and (c) comparing how these consumer segments responded to information about the potential products, origin species, ingredients, and benefits associated with these ingredients. The method used in this study was a consumer survey (n = 490) that led to a consumer segmentation, followed by a conjoint experiment. The results show that ingredient source was the most important attribute. Yet, as many of the ingredient sources were novel, both for the carrier product and the consumer, the important part was not exposing consumers to the species that functioned as the ingredient source. The younger female consumers of the Safe Player group were most focused on the ingredient source, whereas the older male segment, called Open Minded, found the carrier product more important. The final segment, the Innovator, found all of the attributes of almost equal importance.